Al-Falsafah al-Akhlāqiyyah ʻInd Ibn Ḥazm al-Andalūsī - Willy Oktaviano (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2007)
Ibn Hazm al-Andalusi was one of the prominent scholars in the Islamic world, especially in parts of the western part of the Islamic world. He was a follower of the major schools of Fiqh Az Zahiriyah. He was a scholar who was very firm in his stance, especially with the principles of monotheism. He is also priority of his logical and his knowledge on his argument. His thoughts are relate to morals of Islam according to his behavior. This paper is examines the thoughts of Ibn Hazm about akhlak Islamiyah.